Chapter 12 - Single-Versus Multigene Transfer Approaches for Crop Abiotic Stress Tolerance - Goel, Parul; Singh, Anil K.
Biochemical, Physiological and Molecular Avenues for Combating Abiotic Stress in Plants is a must-have reference for researchers and professionals in agronomy, plant science and horticulture. As abiotic stress tolerance is a constant challenge for researchers and professionals working on improving crop production, this book combines recent advances with foundational content, thus offering in-depth coverage on a variety of abiotic stress tolerance mechanisms that help us better understand and improve plant response and growth under stress conditions. The mechanisms explored in this book include stress perception, signal transduction and synthesis of stress-related proteins and other molecules.
Keywords: ABIOTIC STRESS TOLERANCE IN PLANTS